SERANGAN Mimegralla coeruleifrons Macquart PADA TANAMAN JAHE DAN PERANANNYA DALAM MEMBAWA PATOGEN PENYAKIT LAYU - RODIAH BALFAS; SUPRIADI SUPRIADI; NURI KARYANI; ENDANG SUGANDI (Jurnal Penelitian Tanaman Industri, 2000)
The attack of Mimegralla coeruleifrons on ginger plants and its role in carrying pathogens of wilt diseaseRhizome flics Mimegralla coeruleifrons (Diplera; Micropezidae) ac frequently oten found in the diseased ginger rhizome caused by Ralstonia solanacearum, bill it has nol been known which one made the irst damage. Experiments were conducted at laboratory and green house of the Research Institute for Spice and Medicinal Cops from September 1998 to I'cbruary 2000. to examine the attack of M coerulefrons on healthy and disease ginger plants and its role in carrying the pauiogen. Hie experiments consisted of three parts, ink-station of the fly in healthy and diseased ginger plants, disease tansmission and detection of R solanacearum in M coeruleifrons larvae and adults, fiingcr plants were grown in pot containing, sterile media The pots were placed in the field and the plants were inoculated with R solanacearum and iininoculatcd. then they were caged or uncaged. Adult lies (33 - 35 pairs) were introduced into the cage. The uncaged plants were allowed to be naturally invested by the flies. Disease transmission used adult Hies which were collected from diseased ginger plantation. The lies were fed with suspension of R solanacearum. then introduced into cages containing healthy ginger plants. The flies were also directly caged on healthy plants Detection of/?, solanacearum in larvae and adults was carried out by isolation on selective medium and ELISA techniques. Results showed that M coerulefrons mostly attacked the inoculated ginger plants. Tliere was no evidence of Iransmission of R solanacearum by the fly. whereas nearly 50% of the ield collected lics carried R solanacearum. These results tend to suggest that the attack of M. coerulerons occured ater the ginger has been infected by wilt disease and the ly can be a carrier of/? solanacearum.